TRANSFORMASI KEPEMIMPINAN KE INOVASI: PERAN KUNCI KNOWLEDGE MANAGEMENT CAPABILITY PADA UMKM DI SURABAYA - Muzakki, Muzakki; Lukmana, Ardiansyah Hendra (STIE Mahardhika, 2025)
This study aims to analyze the effect of transformational leadership (TL) on innovation capability (IC), with knowledge management capability (KMC) serving as a mediating variable among micro, small, and medium enterprises (MSMEs) in Surabaya. A quantitative approach with an explanatory research design was employed by distributing questionnaires to 290 MSME actors across various sectors. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that TL has a positive and significant effect on IC, confirming that transformational leadership fosters the development of an innovative work culture. Moreover, TL also exerts a positive and significant influence on KMC, indicating that transformational leaders play a crucial role in strengthening knowledge management systems through motivation, inspiration, and collaboration. Furthermore, KMC was found to positively and significantly affect IC, suggesting that knowledge management acts as a key catalyst in enhancing innovation within MSMEs. Another important finding demonstrates that KMC significantly mediates the relationship between TL and IC, implying that the impact of transformational leadership on innovation becomes more effective when facilitated by optimal knowledge management practices. Theoretically, this study contributes to the expansion of the literature on the relationship between TL, KMC, and IC in the MSME context, while practically, it provides valuable implications for MSME owners and managers to integrate transformational leadership with reinforced knowledge management in order to achieve sustainable competitive advantage.